Eutrema bulbiferum (Brassicaceae), a new species with bulbils from Hunan, China - Xiao, Yan; Li, Chun; Hsieh, Tung-Yu; Tian, Dai-Ke; Zhou, Jian-Jun; Zhang, Dai-Gui; Chen, Gong-Xi (Phytotaxa, 2015)
Eutrema bulbiferum, a unique new species of Brassicaceae found in the limestone areas of Longshan and Jishou, Hunan, China, is described and illustrated. This species is most similar to E. tenue and E. yunnanense, but can be easily distinguished by its rosulate fleshy bulbils in the leaf axil or near the stem base, fewer ovules per ovary, slightly 4-angled short wand-like silique, and bended silique apex with a beak. E. bulbiferum is categorized into Eutrema by phylogenetic analysis based on the nuclear internal transcribed spacer (ITS). It is also clearly separated from E. tenue and E. yunnanense by the results of both phylogenetic analysis and Principal Component Analysis (PCA) based on morphometric characters.